Strategi Komunikasi Pemasaran Untuk Meningkatkan Room Revenue Di Innside By Melia Hotel Yogyakarta - Elha Linuar Shima Dulang Parancana; Suparwi Suparwi; Emmelia Nadira Satiti (Jurnal Pariwisata Indonesia, 2019)
This study discusses the marketing communication strategy carried out by inside by Melia Hotel of Yogyakarta in the form of a marketing communication strategy and its impact. The purpose of research to know Strategy of Marketing Communication in Innside by Melia Hotel Yogyakarta and the effect of it. The Approach method used is a qualitative approach that is processing data described in order to be eadily understood by readers, and take the data with interview, documentation, and observation. The results of the discussion are the marketing communication strategies carried out namely advertising, Sales Promotion, Public Relationns, Personal Sales Direct Marketing and Marketing startegies, If done well will have impact on the hotel room revenue increase. The conclusion of the research is that the marketing strategy is carried out in accordance with the theory and implemented well, it has an impact althought it still needs to be improved